1997
DOI: 10.1046/j.1365-201x.1997.00142.x
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability in healthy subjects is related to age and gender

Abstract: The effects of age and gender on heart rate variability as measured by spectral and time domain analysis of 24 h ECG recordings were evaluated in 101 healthy subjects, 49 men and 52 women (20-69 years of age). In the frequency domain, total power, very low-frequency power, low-frequency power and high-frequency power were negatively correlated to age (P < 0.001 for all variables). Total power decreased by 30% between 20-29 and 60-69 years of age. In the time domain, SDNN-index, the mean of the standard deviati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

29
115
3
11

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(158 citation statements)
references
References 21 publications
29
115
3
11
Order By: Relevance
“…This adjustment seems justified because it is well known that heart rate variability in healthy subjects is related to age. 26 In the present study, the lowfrequency A-PSD was significantly higher in patients with essential hypertension with neurovascular compression compared with patients with essential hypertension without neurovascular compression, normotensive subjects and patients with secondary hypertension. This finding suggests that neurovascular compression may increase blood pressure via an increase in sympathetic tone.…”
Section: Discussionsupporting
confidence: 46%
“…This adjustment seems justified because it is well known that heart rate variability in healthy subjects is related to age. 26 In the present study, the lowfrequency A-PSD was significantly higher in patients with essential hypertension with neurovascular compression compared with patients with essential hypertension without neurovascular compression, normotensive subjects and patients with secondary hypertension. This finding suggests that neurovascular compression may increase blood pressure via an increase in sympathetic tone.…”
Section: Discussionsupporting
confidence: 46%
“…Decreased values of HF, TP, SDNN, RMSSD, mean RR, and pNN50 and increased values of LF and LF/HF was noted with advancement of age. Jensen-Ustad et al (1997) observed that progression of age lowered the values of heart rate variability and shifted the individual towards sympathodominance. TP, the principal index of general sympathovagal tone, exhibited a significant negative correlation with age.…”
Section: Discussionmentioning
confidence: 98%
“…The above-mentioned theories can explain physiological changes, which occurs with advancement of age. Cardiovascular aging in terms of decline in maximum heart rate, oxygen extraction, aerobic capacity, arterial stiffening, vasoconstriction, elevated systolic blood pressure, thickening of the left ventricle wall, reduced diastolic filling rate, impaired cardiac reserve, alterations in heart rate rhythm, and prolonged cardiac action potential were described earlier by different researcher (Landahl et al 1986;Reardon and Malik 1996;Jensen-Ustad et al 1997). Aging was found to be directly associated with structural and functional changes in autonomic nervous system (ANS).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Studies have shown that the process of physiological aging leads to HRV reduction 1,[3][4][5] , related to a decrease of the vagal actuation over the sinusal node 1,3 , which is, in turn, associated to the increase on morbidity and mortality originated from different causes, in addition to coronary arterial disease, in both middle-aged and elderly individuals 5 . In this context, some works have analyzed the effects of sedentary life-style changes, through implementation of physical exercise programs in the attempt to minimize or partially reverse the HRV decrease that occurs with aging [6][7][8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%